DETERMINATION OF TRACE ELEMENTS USING NANOCOMPOSITES FROM HETEROATOM-DOPED REDUCED GRAPHENE OXIDE - ALI, AHMAD SORAN ALI (Fırat Üniveristesi, 2026)
The primary objective of this thesis is to synthesize and characterization of nanocomposite from heteroatom doped-reduced graphene oxide. For this purpose, heteroatom-reduced graphene oxide including B, N-rGO were transformed into nanocomposites using PVDF polymer. The obtained nanocomposite materials were characterized using FTIR, SEM and TGA and, after that, used in determination of trace elements in water samples. To obtain nanocomposite materials, the rGO derivatives and PVDF solutions were ultrasonicated and after that mixed at 80 oC. After grinding of dried nanocomposite they used as –adsorbents to preconcentrate trace elements including Cr, Ni and Cd at ppb levels. For metal determinations, ICP-MS was used. It was found that the optimum conditions for preconcentration were pH=5 and contact time=45 min. In addition, achieving of environmentally friendly preconcentration method in chemical analysis was achieved in this study. From the obtained results for natural waters, it was concluded the metal concentrations are lower than the allowable values.

Bu tezin temel amacı, heteroatom katkılı indirgenmiş grafen oksitten nanokompozit sentezlemek ve karakterizasyonunu sağlamaktır. Bu amaçla, B, N-rGO içeren heteroatom indirgenmiş grafen oksit, PVDF polimeri kullanılarak nanokompozitlere dönüştürülmüştür. Elde edilen nanokompozit malzemeler, FTIR, SEM ve TGA ile karakterize edildi ve daha sonra su örneklerindeki eser elementlerin tayininde kullanılmıştır. Nanokompozit malzemeler elde etmek için, rGO türevleri ve PVDF çözeltileri ultrasonikasyona tabi tutulmuş ve ardından 80 oC'de karıştırılmıştır. Kurutulmuş nanokompozit öğütüldükten sonra, eser metalleri ppb seviyelerinde önderiştirmek için adsorban olarak kullanılmıştır. Cr, Ni ve Cd u içeren metal tayinleri için ICP-MS kullanılmıştır. Önderiştirme için optimum koşulların pH = 5 ve temas süresi = 45 dakika olduğu bulunmuştur. Ayrıca, bu çalışmada kimyasal analizde çevre dostu bir önderiştirme yöntemi elde edilmiştir. Doğal sular için elde edilen sonuçlardan, metal konsantrasyonlarının izin verilen değerlerin altında olduğu sonucuna varılmıştır.
Heteroatom katkili indirgenmiş grafen oksitten nanokompozitler kullanilarak eser elementlerin belirlenmesi
Keywords: Kimya